Feelings of nurses in the reception and risk classification evaluation in the emergency room - Andressa Midori Sakai; Mariana Angela Rossaneis; Maria do Carmo Fernandez Lourenço Haddad; Denise da Silva Scaneiro Sardinha (Rev Rene)
Objective: to reveal feelings of nurses who host with risk assessment and classification in an emergency room of a pubic hospital. Methods: it is a qualitative research approach with 12 nurses interviewed. The data were analyzed, categorized and discussed according to the theoretical framework of work psychodynamics. Results: the nurses expressed feelings of satisfaction in meeting the user needs assistance. They reported feeling as fear, stress and fatigue due to the sharp pace of work, gaps in health care network and situations of violence. They highlighted coping strategies to reduce the burden of this assignment, how to share the completion of the screening with the nursing staff. Conclusion: the host with risk assessment and classification favors the autonomy of nurses and provide greater accountability to this professional users, but the limitations of available resources to solve the complaint of patients generate physical and psychological burden to this worker.